SUSTAINABLE BENCHMARKS FOR TOURIST ACCOMMODATIONS IN BALI - Ni Made Utami Dwipayanti (Environmental Research Center (PPLH) of Udayana University)
As part of our efforts to move towards sustainable development, it is very importantto encourage the tourism industry to be more environmentally conscious because itconsumes large amounts of resources. One way of achieving greater sensitivity is to identifybenchmarks for energy and water use and for other aspects of hotel operations like theamount of solid waste generated. Benchmarks can be defined using data from existinghotels. The research project focused on tourist accommodation on Southern Part of BaliIsland. It conducted a survey by mailed questionnaire of about 50% of the hotels on theisland. The questionnaire obtained annual data on several sustainability criteria that areenergy and water consumption, biodiversity conservation, resource conservation, cleaningchemical use, solid waste management and wastewater management. The data were usedto derive baseline and best practice thresholds to improve the performance of touristaccommodation on Bali Island.The benchmarks, both baseline and best practice standards were developed mainlyusing the study results which established the average and the average of the top 25% ofperformers. The average of the top 10% of performers was also considered in selecting thebest practice standard for indicators that required stricter standards. Within thebenchmarking process, Green Globe 21 standards and some other studies were also beingused for comparison purpose.In this survey, the difficulties were found in obtaining complete set of data from eachrespondents as well as gaining sufficient responses. Few hotels provided complete set ofdata. Data on energy and water consumption is the easiest to obtain, while data for otherindicators only provided by less than 75% of respondents. Most of the survey resultsshowed reasonable value compared to Green Globe 21 standards. Good performance oftourist accommodation in the survey was found in energy consumption indicator that theaverage and the average of the top 25% of performers were far stricter than the Green Globe21 standards. The study concluded with benchmarks recommendation for each indicatorthat can be applied to tourist accommodations in Southern Part of Bali Island.